Is the Reaction of C3N(-) with C2H2 a Possible Process for Chain Elongation in Titan's Ionosphere? - Lindén, Fredrik; Alcaraz, Christian; Ascenzi, Daniela; Guillemin, Jean-Claude; Koch, Leopold; Lopes, Allan; Polášek, Miroslav; Romanzin, Claire; Žabka, Jan; Zymak, Illia; Geppert, Wolf D (The journal of physical chemistry. A, 2016)
The reaction of C3N(-) with acetylene was studied using three different experimental setups, a triple quadrupole mass spectrometer (Trento), a tandem quadrupole mass spectrometer (Prague), and the "CERISES" guided ion beam apparatus at Orsay. The process is of astrophysical interest because it can function as a chain elongation mechanism to produce larger anions that have been detected in Titan's ionosphere by the Cassini Plasma Spectrometer. Three major products of primary processes, C2H(-), CN(-), and C5N(-), have been identified, whereby the production of the cyanide anion is probably partly due to collisional induced dissociation. The formations of all these products show considerable reaction thresholds and also display comparatively small cross sections. Also, no strong signals of anionic products for collision energies lower than 1 eV have been observed. Ab initio calculations have been performed to identify possible pathways leading to the observed products of the title reaction and to elucidate the thermodynamics of these processes. Although the productions of CN(-) and C5N(-) are exoergic, all reaction pathways have considerable barriers. Overall, the results of these computations are in agreement with the observed reaction thresholds. Due to the existence of considerable reaction energy barriers and the small observed cross sections, the title reaction is not very likely to play a major role in the buildup of large anions in cold environments like the interstellar medium or planetary and satellite ionospheres.